Contents of Education for Sustainable Development - D S Ermakov (Peoples' Friendship University of Russia (RUDN University), 2013)
The essence of education for sustainable development (ESD) has been disclosed in this article. The definition of ESD has been formulated. The key approaches to the formation of the ESD curriculum have been designated. The criteria for selecting the content of ESD have been proposed. The feasibility of applying the competency based approach has been shown.